Comparative analysis of phytochemical constituents, antibacterial and antioxidant activity of green tea : camellia sinensis - Rahman, Ilma (BRAC University, 2016)
This Thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2016.